Practical percussion a guide to the instruments and their sources - Holland, James (Scarecrow Press, 2005)
The second half of the twentieth century saw vast changes in all aspects of percussion - the instruments themselves, playing techniques, and percussion writing - plus the huge influence of pop music, jazz, and film scores. Additionally, the revolution in travel and communications has meant that composers have become much more aware of a seemingly endless variety of ethnic instruments from around the world. Holland aims to show the world of percussion as it is today, and to answer some common questions about it. Today's professional players frequently find themselves performing in many countries where the availability of percussion instruments can vary widely. Practical Percussion contains a section on manufacturers and suppliers all over the world. In addition to this list of manufacturers, the percussion requirements - both instruments and players - for some 1500 works are also listed. The foreword by Pierre Boulez further assists the reader in appreciating and understanding the richness, variety, and function of percussion instruments the world over.